Production of Liquid Organic Fertilizer from Pineapple Peel Waste Using EM4 as a Bioactivator - Mandasari, Weni; Prawiranti, Yulizar; Shofiyah, Sofi Siti; Febriaty, Irma Ramadhani; Utami, Naniek Tri (Jurnal Kimia Fullerene, 2025)
Pineapple peel waste is an abundant agricultural residue that remains underutilized. This study aims to produce liquid organic fertilizer (LOF) from pineapple peels using EM4 bioactivator, cow manure, rice-washing water, and palm sugar through a 30-day fermentation process. Fermentation performance was monitored via daily temperature and pH, along with nutrient content analysis including nitrogen (N), phosphorus (P), potassium (K), and organic carbon (C-organic). The results showed temperature ranged from 27.9–32.3°C and pH between 3.0–4.0, within the optimal range for microbial activity. However, nutrient concentrations of N (0.153%), P (0.116%), K (0.105%), and C-organic (1.58%) did not meet the Indonesian National Standard (SNI 261/2019). This indicates that pineapple peel alone requires nutrient-rich additives to produce standard-compliant LOF. This study highlights the potential of pineapple peel waste as an eco-friendly LOF source, emphasizing the need for further formula optimization.